Relationships between monocyte count to high-density lipoprotein cholesterol ratio and cardiovascular outcomes in patients commencing dialysis. Issue 11 (November 2021) - Kim, Dongryul; Kim, Da Won; Lee, Yeon Hee; Park, So Yeon; Song, Young Woo; Shin, Hyeonoh; Yoon, Hye Eun; Park, Hoon Suk; Choi, Bum Soon; Kim, Byung Soo; Ban, Tae Hyun; Shin, Seok Joon
Objective: High monocyte to high-density lipoprotein cholesterol ratio (MHR) is known to be a risk factor for cardiovascular (CV) complications. We aimed to evaluate the relationship between MHR and CV outcomes in patients commencing dialysis. Methods: The medical records of patients who started maintenance dialysis between January 2006 and July 2017 were reviewed. The primary outcomes were all-cause mortality and overall CV mortality and the secondary outcomes were CV event-free survival and the incidence of CV complications. Results: Five hundred ninety-seven patients were enrolled and allocated to low- or high-MHR groups. All-cause mortality did not differ between the groups during a mean follow-up period of 3.9 years. In addition, overall CV mortality did not differ between the groups. However, CV event-free survival was significantly lower in the high-MHR group than in the low-MHR group (47.5% vs . 59.0%). Multivariate Cox regression analysis showed that high MHR was an independent predictor of CV events (HR 1.886, 95% CI 1.015–3.505). Conclusion: High MHR at the time of initiation of dialysis may represent a useful predictor of CV complications.